Tom Slade at Bear Mountain - Fitzhugh, Percy Keese, 1876-1950; Hastings, Howard L. (Howard Livingston), 1887-1955 (Salt Lake City, UT : Project Gutenberg, 2023)
"Tom Slade at Bear Mountain" by Percy Keese Fitzhugh is a novel written in the early 20th century. The story follows Tom Slade, a young adventurer involved with the Boy Scouts, as he embarks on a series of thrilling escapades that begin with a visit to his Aunt Martha and lead him into an exploration of hidden treasures, mysterious characters, and encounters with outlaws. The narrative promises adventure and exploration, appealing to readers who enjoy tales of brave youths and the outdoors. The opening of the book sets the stage for the protagonist's journey, starting with Tom's reflective thoughts about visiting his aunt in Kingston, New York. As he travels through picturesque landscapes, he becomes captivated by the wilderness that surrounds him, filled with treachery and romance akin to tales of old bandits and outlaws. Tom$1 (Bs curiosity is piqued upon learning about the local history of treasure and crime in the area, particularly through his meeting with Long Buck Sanderson, an eccentric character who shares tales of his past adventures. This sets in motion Tom's unintentional plunge into a world of hidden treasure and aging legends, hinting at the adventures yet to unfold in his excursion. (This is an automatically generated summary.)s
Release date is 2023-11-20
Roger Frank and Sue Clark
Keywords: Camping -- Juvenile fiction; Boy Scouts of America -- Juvenile fiction; New York (State) -- Juvenile fiction